The pathway to comfort: Role of palliative care for serious COVID-19 illness - Rao, Krithika S. (Indian J Med Sci, 2020)
The novel coronavirus disease (COVID-19) pandemic has led to significant distress among people of all age groups. Patients with advanced age and severe life-limiting illnesses are at increased risk of death from COVID-19. Not all patients presenting with severe illness will be eligible for aggressive intensive treatment. In limited resource setting, patients may be triaged for supportive care only. This subset of patients should be promptly identified and receive appropriate palliative care with adequate symptom control strategies and psychosocial support. Breathlessness, delirium, pain, and noisy breathing are main symptoms among these patients which can add to the suffering at end-of-life. The COVID-19 pandemic also contributes to the psychological distress due to stigma of the illness, uncertainty of the illness course, fear of death and dying in isolation, and anticipatory grief in families. Empathetic communication and holistic psychosocial support are important in providing good palliative care in COVID-19 patients and their families.